Study of fabomotizole effect on the behavioral disorders in rat offsprigs exposed to tabaco smoke and ethanol - A. S. Solomina; E. D. Shreder; L. G. Kolik; A. D. Durnev (LLC "Publisher OKI", 2018)
Assessment of fabomotizole effects on postnatal development of newborn and adult rat offspring after maternal ethanol or cigarette smoke exposure was performed. The experiments were carries out in outbred pregnant rats housed in the vivarium of FSBI "Zakusov Institute of Pharmacology". Each group included at least 10 animals. Ethanol (4.3 ml/kg, 40 % vol.) was administered per os from 10 to 19 days of pregnancy; exposure to cigarette smoke from 4 cigarettes with filter (13 mg of tar and 1 mg nicotine) was performed throughout the pregnancy once a day. Fabomotizole (1 and 10 mg/kg, daily) was administered per os in all experiments. The unconditional reflexes formation and muscle strength were evaluated on postnatal day 5. The same animals were examined in the tests «T-shaped maze» and «extrapolation disposal» to assess cognitive functions after postnatal day 60. These studies demonstrated the ability of fabomotizole to prevent or reduce postnatal abnormalities of rats exposed to ethanol or tobacco smoke in utero. The results show the potential opportunity of using fabomotizole for prevention of delay physical development, learning and memory.